2016
DOI: 10.1080/10601325.2016.1189278
|View full text |Cite
|
Sign up to set email alerts
|

Novel copolymers of styrene. 14. Halogen ring-trisubstituted butyl 2-cyano-3-phenyl-2-propenoates

Abstract: Novel trisubstituted ethylenes, halogen ring-trisubstituted butyl 2-cyano-3-phenyl-2-propenoates, RPhCH HC(CN)CO 2 C 4 H 9 (where R is 3-bromo-4,5-dimethoxy, 5-bromo-2,4-dimethoxy, 2-bromo-3-hydroxy-4-methoxy, 3-chloro-2,6-difluoro, 4-chloro-2,6-difluoro, 2,3,5-trichloro, 2,3,6-trichloro, 2,4,5-trifluoro) were prepared and copolymerized with styrene. The monomers were synthesized by the piperidine catalyzed Knoevenagel condensation of ring-substituted benzaldehydes and butyl cyanoacetate, and characterized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The conversion of the copolymers was kept between 10 and 20% to minimize compositional drift (Table 1). Nitrogen elemental analysis showed that between 9.2 and 34.5 mol% of OPCA is present in the copolymers prepared at ST/ OPCA = 3 (mol), which is indicative of relatively high reactivity of the OPCA monomers towards ST radical which is typical of ring-substituted 12 OPCA [18][19][20][21][22][23][24][25][26]. Since OPCA monomers do not homopolymerize, the most likely structure of the copolymers would be isolated OPCA monomer units alternating with short ST sequences (Scheme 2).…”
Section: Synthesis and Characterization Of Styrene -Opca Copolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…The conversion of the copolymers was kept between 10 and 20% to minimize compositional drift (Table 1). Nitrogen elemental analysis showed that between 9.2 and 34.5 mol% of OPCA is present in the copolymers prepared at ST/ OPCA = 3 (mol), which is indicative of relatively high reactivity of the OPCA monomers towards ST radical which is typical of ring-substituted 12 OPCA [18][19][20][21][22][23][24][25][26]. Since OPCA monomers do not homopolymerize, the most likely structure of the copolymers would be isolated OPCA monomer units alternating with short ST sequences (Scheme 2).…”
Section: Synthesis and Characterization Of Styrene -Opca Copolymersmentioning
confidence: 99%
“…Thus, copolymerization of electrophilic TSE monomers having double bonds substituted with halo, cyano, and carbonyl groups and electron-rich monosubstituted ethylenes such as styrene, N-vinylcarbazole, and vinyl acetate [16][17][18] show a tendency toward the formation of alternating copolymers -thus suggesting a way of functionalization of commercial polymers via introduction of isolated monomer units in copolymers. Earlier we have reported synthesis and styrene copolymerization of several ring-monosubstituted methyl [19][20][21], ethyl [22], propyl [23,24], isopropyl [25], butyl [26], isobutyl [27], and 2methoxyethyl [28] PCAs.…”
mentioning
confidence: 99%
“…ring-substituted TSE monomers, 3-phenyl-2-dicyanoethenes (Kharas 2011) and butyl 3-phenyl-2-cyano-2-propenoates (Kharas 2016) were copolymerized with 4-flourostyrene and styrene, respectively. With the objective to design novel structures, that could serve as a spring board for further development of novel materials with new properties and applications, and in continuation of our studies of the monomer structure-reactivity correlation in the radical copolymerization of TSE monomers we have prepared ring-trisubstituted propyl 2-cyano-3-phenyl-2-propenoates (PCPP), RPhCH=C(CN)CO 2 C 3 H 7 , where R is 2, 3,6-trichloro, 2,3,4-trifluoro, 2,3,5-trifluoro, 2,4,5-trifluoro, 2,4,6-trifluoro, 3,4,5-trifluoro, and explore the feasibility of their copolymerization with styrene.…”
Section: Similarlymentioning
confidence: 99%
“…We continue to explore synthesis and copolymerization of CPP compounds; thus, we have prepared and copolymerized with vinyl benzene ring-trisubstituted methyl [15], ethyl [16], propyl [17,18], and butyl [19,20] esters of 2-cyano-3-phenyl-2-propenoic acid. Recently we have reported synthesis and vinyl benzene copolymerization of a number of novel chloro and methoxy [21] and dimethoxy [22] ring-disubstituted isopropyl esters of 2-cyano-3-phenyl-2-propenoic acid.…”
Section: Introductionmentioning
confidence: 99%